Taming the People: Comparing Protests and Populism in Arab and American Politics - Khamis, Sahar; Fowler, Randall (Frontiers in Communication, 2022)
The rise of populism has been an uncontested global reality in recent years. However, it is unclear exactly how culturally distinct populist movements imitate or mirror each other, especially given the different rhetorical, political, ideological, and cultural contexts within which they operate. This article addresses this issue by comparing recent manifestations of populism across contemporary Arab and American contexts, with a special focus on former U.S. President Donald Trump’s response to the George Floyd protests and Egyptian President Abdel Fatah el-Sisi’s handling of demonstrations in his country. We argue that each leader deployed common rhetorical tactics as a populist strategy to undermine the protestors’ attempts to articulate the people’s will. At the same time, our analysis shows how the different contexts in which Trump and Sisi operate also impact their ability to successfully translate their populism into political effectiveness. By conducting this analysis, our article shows how similar populist tactics across different cultural contexts may lead to divergent outcomes, revealing the importance of institutional as well as popular bases of support for would-be populist politicians.